Pecking order theory of capital structure: empirical evidence from dynamic panel data - Tunde, Matemilola Bolaji; Amin Noordin, Bany Ariffin (Global Science and Technology Forum, 2011)
This paper tests the relation between profit and long term debt as well as the relation between profit and total debt in South Africa. This paper specifies a dynamic panel model and uses generalized method of moments (GMM) estimation technique which gives better results. The results show that profit has significance negative relation with long-term debt. Similarly, profit has significant negative relation with total debt. The results support the pecking order theory and signify the presence of asymmetric information problem between firm and its financiers. Besides, the results imply need to further develop the capital market in order to minimize information asymmetry costs associated with raising external capital. Moreover, evidence of trade-off theory is also present in the results.